Late Prof. Dr. Md. Anwar Hossain (August 19, 1944 - May 27, 2021) - Alim, Md Abdul (Journal of Bangladesh Academy of Sciences, 2021)
Abstract not available J. Bangladesh Acad. Sci. 45(1); 1-11: June 2021